Does the parole program affect recidivism? Qualitative Analysis in Malaysia - S. Syamsulang; М. Huzaini (Russian Journal of Economics and Law)
Objective: the objective of this study is to identify the critical factors that present challenges and opportunities for parolees in Malaysia to avoid committing repeated crimes and reduce recidivism.Methods: the study employs a qualitative approach, using face-to-face interviews with prison officers in the state of Pahang, Malaysia, to gather data. Content analysis is used to analyse the data and identify the critical factors for parole activities in Malaysia.Results: the study identified five crucial factors that affect parole activities in Malaysia: individuals, families, communities, private institutions, and government policies. Individuals refer to the characteristics and behavior of the parolee, while families and communities relate to the support and involvement of the parolee’s family and community in the rehabilitation process. Private institutions, such as Intermediate Houses and Corporate Smart Internship (CSI), can provide support and resources for parolees, and effective government policies and practices can ensure successful reintegration into society. Further studies could investigate the specific ways in which these factors influence parole activities in Malaysia and explore best practices for reducing recidivism rates.Scientific novelty: this study contributes to the literature on parole activities in Malaysia by identifying critical factors that can impact the success of the parole system in reducing recidivism. The study provides valuable insights into the challenges and opportunities faced by parolees in Malaysia.Practical significance: the findings of this study can be used by the Malaysian Prisons Department to develop effective strategies and policies to reduce recidivism rates and improve the success of the parole system. The study can also be used by other countries with similar parole systems to identify critical factors that impact the success of their parole programs.